(untitled) (Eurasian Journal of Philology Science and Education, 2016)
Since the period of year of independence in the Kazakh linguistics it is considered advertizing languages. Because, in this period the republic passed ours to market society. Now life of the modern person is inconceiv able without advertizing background which is more and more obvious, more active and acting. The advertizing which got and getting into all spheres of society actively influences its social institutes and has considerable impact on social behavior of the people living in it. Estimated value in linguistics is reflected in the different language levels and are used to achieve the objectives of the communicants. The most basic units forming the estimated value, are part of speech. Adjective – the derived transmission path estimated value in advertising in the Kazakh language. Categories comparative degree of adjectives, lexical group are owners of the estimated value of any kind of advertising (+, ). The article is an analysis on a group of words, which are considered an integral part of society, with estimates made using the adjective and the findings were made by scientists.